Digital marketing in higher education: Role and prospects - Sadikov, Shokhrukh (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the role, significance, and future prospects of digital marketing in higher education institutions, with a particular focus on student behavior, emerging digital technologies, and the national context of Uzbekistan. Research Methodology: This research employs inductive and deductive approaches using secondary data from international reports (Statista, DataReportal, OECD), national statistics from Uzbekistan, and comparative analysis of higher education digital marketing practices. The methods include comparative analysis, statistical analysis, trend analysis, and case studies of selected universities. Results: The findings reveal that 70% of higher education institutions increased their digital marketing budgets in 2024. Video content influences 84% of students’ university choices, while 75% of prospective students rely on social media for information. In Uzbekistan, internet penetration reached 83.3%, and higher education coverage increased to 43%, indicating strong potential for digital marketing expansion. However, many universities still depend on traditional marketing methods and lack structured SEO and CRM strategies. Conclusions: Digital marketing has become a strategic instrument for enhancing student recruitment, institutional competitiveness, and global visibility. Artificial intelligence, video marketing, personalized communication, and virtual campus tours will dominate future digital marketing practices in higher education. Limitations: This study relies on secondary data and descriptive analysis without primary survey or experimental validation, limiting causal statistical inference. Contribution: This study contributes to the limited literature on digital marketing in higher education in Uzbekistan and provides practical strategic insights for universities and policymakers in developing digital-based recruitment systems.